Growth of Gracilaria under Different Planting Distances in Pond - . Sunarto (Jurnal Akuakultur Indonesia)
The use of non-productive shrimp ponds for cultivation of Gracilaria is one of the strategies that can be performed to achieve production target of seaweed. This study was conducted to determine the influence of different planting distances on growth of Gracilaria cultivated in pond. Gracilaria was separately planted in distant of 20x20 cm; 25x25 cm; 30x30 cm and 35x35 cm in pond for 45 days cultivation.  Relative growth rate and thallus length increment were measured to obtain an optimal planting distance. The results of study showed that 25x25 cm planting distance resulted in a higher relative growth rate (137.8%) and increment of thallus length (15.3%) compared with other treatments.  Thus, cultivation of Gracilaria in an unproductive pond with 25x25 cm planting distance may improve production.